Pengaruh Perkembangan Wilayah Pinggiran Kota Yogyakarta terhadap Perkembangan Desa Wisata Tanjung, Desa Donoharjo, Kecamatan Ngaglik, Kabupaten Sleman - Salsabila, Najma; Purwohandoyo, Joni (Universitas Diponegoro, Indonesia, 2020)
Tanjung Tourism Village is one of the tourist villages in the suburbs of Yogyakarta. The village is traversed by the Palagan Tentara Pelajar street which is the main road connecting Tanjung Tourism Village with the City of Yogyakarta. Palagan Tentara Pelajar street is now increasingly showing urban traits with lots of land being built that are used for trade, industry, services, and settlements. The existence of this case Tanjung Tourism Village is vulnerable to the development of the surrounding region. The research aims to analyze the development factors of the urban area which influenced the development of Tanjung Tourism Village. The approach used is a quantitative approach with 35 land polygons that are converted into built-up land from the results of image interpretation. The results showed that the development factors of urban areas affected the development of Tanjung Tourism Village namely: internal factors in the form of (1) community economic factors and (2) kinship social factors and external factors in the form (1) low land prices in Tanjung Tourism Village, ( 2) strategic location and easy accessibility, (3) proximity to the workplace, and (4) proximity to the center of activity.